DECISION SUPPORT SYSTEM IN DETERMINING THE BEST JUDO ATHLETE USING AHP METHOD - Kristiyanti, Dinar Ajeng; Pangemanan, Garth Wishnuwardhana (Jurnal Pilar Nusa Mandiri, 2020)
To determine the best Judo athlete, Rajawali Judo Club of Battalion Arhanud 1 Divif 1 Kostrad has several obstacles such as making a decision in determining the best Judo athlete by the Coach and the Achievement Development which only based on experience which is estimated without the existence of any system. This results in subjectivity and the absence of a strong basis for competent objective decision making which then triggers gaps between athletes. The absence of specific criteria creates that result in not targeting the selection of the best Judo athletes. For this reason, a method, in this case, is needed to choose the AHP (Analytical Hierarchy Process) method and a number of criteria as indicators in determining the best Judo athlete. While the referenced criteria are Self-Dropping Technique (Ukemi), Slamming Technique (Nage-waza), Lockdown or Lying Technique (Katame-waza), Discipline and Achievement. The purpose of this study is expected to produce statistical data as an evaluation material for the training team to minimize or even eliminate the gap between fellow Judo athletes at the Rajawali Judo Club of Battalion Arhanud 1 Divif 1 Kostrad. The result of this study is based on Analytical Hierarchy Process calculations, obtained the most important priority criteria in determining the best Judo athlete in which the Achievement criteria with value 0.325 or equivalent to 32%, then followed by Disciplinary criteria with value 0.227 or equivalent to 23%, Slamming Technique criteria (Nage-waza) with value 0.211 or equivalent to 21%, Lockdown/Laying Technique criteria (Katame-waza) with value 0.125 or equivalent to 12% and in the last rank the Self-Dropping Technique criteria (Ukemi) with value 0.112 or equivalent to 11%.